Use of a Green Fluorescent Strain for Analysis of Xylella fastidiosa Colonization of Vitis vinifera - Newman, Karyn L. (American Society for Microbiology, 2003)
Xylella fastidiosa causes Pierce's disease of grapevine as well as several other major agricultural diseases but is a benign endophyte in most host plants. X. fastidiosa colonizes the xylem vessels of host plants and is transmitted by xylem sap-feeding insect vectors. To understand better the pattern of host colonization and its relationship to disease, we engineered X. fastidiosa to express a green fluorescent protein (Gfp) constitutively and performed confocal laser-scanning microscopic analysis of colonization in a susceptible host, Vitis vinifera. In symptomatic leaves, the fraction of vessels colonized by X. fastidiosa was fivefold higher than in nearby asymptomatic leaves. The fraction of vessels completely blocked by X. fastidiosa colonies increased 40-fold in symptomatic leaves and was the feature of colonization most dramatically linked to symptoms. Therefore, the extent of vessel blockage by bacterial colonization is highly likely to be a crucial variable in symptom expression. Intriguingly, a high proportion (>80%) of colonized vessels were not blocked in infected leaves and instead had small colonies or solitary cells, suggesting that vessel blockage is not a colonization strategy employed by the pathogen but, rather, a by-product of endophytic colonization. We present evidence for X. fastidiosa movement through bordered pits to neighboring vessels and propose that vessel-to-vessel movement is a key colonization strategy whose failure results in vessel plugging and disease.